Application of Solar Radiation Analysis Technology in the Optimization of Campus Planting Design. Issue 1 (April 2021) - Hsu, Che-Yu; Ou, Sheng-Jung
Abstract: In recent years, the slogans and concepts of sustainable campus, eco-campus, and environmental protection campus have been continually put forward, but there is little ink about the maintenance and management of the most important plants on campus. However, landscape designers often neglect the requirements of plants for the growth conditions of sunlight, or the impact of surrounding buildings on the living environment of plants, resulting in an irreversible situation. To this end, this research hopes to use environmental analysis aided design software to simulate the solar radiation environment and provide references for campus planting design and suggestions for plant selection. The results show that sciophytes are suitable for planting in areas where solar radiation energy is less than 2.90 MJ/m 2 d; Heliophytes are suitable for planting in areas where solar radiation energy is greater than 5.40 MJ/m 2 d, and the area in between is suitable for planting mesophytes.